COVID-19: Medidas preventivas: Lavando y desinfectando bolsas reutilizables - Michelle Danyluk; Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman (EDIS)
This is the Spanish-language version of FSHN20-24/FS354: COVID-19 Preventative Measures: Cleaning and Disinfecting Reusable Bags.